Proteomic Analysis of Fetal Ovaries Reveals That Primordial Follicle Formation and Transition Are Differentially Regulated. (7th February 2017) - Xu, Mengmeng; Che, Long; Yang, Zhenguo; Zhang, Pan; Shi, Jiankai; Li, Jian; Lin, Yan; Fang, Zhengfeng; Che, Lianqiang; Feng, Bin; Wu, De; Xu, Shengyu
Abstract : Primordial follicle formation represents a critical phase of the initiation of embryonic reproductive organ development, while the primordial follicle transition into primary follicle determines whether oestrus or ovulation will occur in female animals. To identify molecular mechanism of new proteins which are involved in ovarian development, we employed 2D-DIGE to compare the protein expression profiles of primordial follicles and primary follicles of fetal ovaries in pigs. Fetal ovaries were collected at distinct time-points of the gestation cycle (g55 and g90). The identified proteins at the g55 time-point are mainly involved in the development of anatomical structures [reticulocalbin-1 (RCN1), reticulocalbin-3 (RCN3)], cell differentiation (actin), and stress response [heterogeneous nuclear ribonucleoprotein K (HNRNPK)]. Meanwhile, at the g90 stage, the isolated proteins with altered expression levels were mainly associated with cell proliferation [major vault protein (MVP)] and stress response [heat shock-related 70 kDa protein 2 (HSPA2)]. In conclusion, our work revealed that primordial follicle formation is regulated by RCN1, RCN3, actin, and HNRNPK, while the primordial follicle transformation to primary follicle is regulated by MVP and HSPA2. Therefore, our results provide further information for the prospective understanding of the molecular mechanism(s) involved in the regulation of the ovarian follicle development.